1954
DOI: 10.1139/v54-120
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Hydroxylamines as Organo-Analytical Reagents

Abstract: 'The investigation of the use, as analytical precipitants, of a number of aromatic phenyll~ydrosylamines is described. In general they react similarly, increasing in selectivity with an increase in acidity of the oxime group. In acid solutions (lye or more) only vanadium, tin, titanium, and zirconiun~ are precipitated. Their variation in reaction with copper and the nature of their reaction with tin are described. All conlpounds can act as osidants or reductants with an oxidation potential of approsimately -1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1962
1962
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…Solubility data for only a few compounds are available in literature. Values for solubility of iV-phenylbenzohydroxamic acid, iV-phenyl-l-naphthohydroxamic acid, and iV-phenyl-3,5-dinitrobenzohydroxamic acid reported here are in general agreement with the values reported by earlier workers (3,7), but there is an unaccountable disagreement in the values for JV-phenyl-2furohydroxamic acid and iV-l-naphthylbenzohydroxamic acid.…”
supporting
confidence: 90%
“…Solubility data for only a few compounds are available in literature. Values for solubility of iV-phenylbenzohydroxamic acid, iV-phenyl-l-naphthohydroxamic acid, and iV-phenyl-3,5-dinitrobenzohydroxamic acid reported here are in general agreement with the values reported by earlier workers (3,7), but there is an unaccountable disagreement in the values for JV-phenyl-2furohydroxamic acid and iV-l-naphthylbenzohydroxamic acid.…”
supporting
confidence: 90%
“…No other reductions of hydroxamic acids by metal ions have been characterized. Lutwick and Ryan'observed the oxidation of V(II) to V(IV}, Ti(III) to Ti(IV) and Sn(II) to Sn{IV) by several hydroxamic acids in dilute aqueous solution 64. However,·they did not take special precautions against oxygen and it was later shown that oxygen was responsible for the oxidation of Sn(II) and not the hydroxamic acids.…”
mentioning
confidence: 99%
“…(1a), [20] N-hydroxy-N-(4-nitrophenyl)-acetamide (1b), [21] N-(4-cyanophenyl)-N-hydroxyacetamide (1c), [22] N-(4-acetylphenyl)-N-hydroxyacetamide (1d), [23] N-hydroxy-N-(4-hydroxyphenyl)acetamide (1e), [23,24] N-hydroxy-N-phenyl-4-methoxybenzamide (2b), [25,26] N-hydroxy-N-phenyl-4-nitrobenzamide (2c), [25,27] N-hydroxy-N-phenyl-1-naphthamide (3), [28,29] and N,NЈ-dihydroxy-N,NЈ-diphenylterephthalamide (5), [30] were prepared by acylation of the corresponding N-arylhydroxylamines with the corresponding acid chlorides according to the procedure described for AHA 1a in ref. [20] All crystalline compounds were identified by 1 H NMR, 13 C NMR, and by the melting points given in the literature.…”
Section: N-hydroxyacetanilidementioning
confidence: 99%